2018
DOI: 10.22578/ijms.16.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 Single Nucleotide Polymorphism C-590t Polymorphisms in Relation to Asthma

Abstract: Background: Single nucleotide polymorphisms in the promoter regions of genes encoding for some interleukins may associate with occurrence of asthma. Objective: To investigate the association of single nucleotide polymorphisms of interleukin-4 (IL-4) (C-590T) and asthma. Methods: Forty-five patients with asthma and 40 apparently healthy subjects (represent the control group) were enrolled in this study. Blood samples were collected from both patients and controls. DNA was extracted from blood samples and gene f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The initial screening excluded studies that failed to meet the inclusion criteria. After ltering by availability and reading, consisting of reading the title, abstract, and keywords of each study, ve articles were selected [10][11][12][13][14] . The study selection process was visually presented in Fig.…”
Section: Characteristics and Quality Of Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial screening excluded studies that failed to meet the inclusion criteria. After ltering by availability and reading, consisting of reading the title, abstract, and keywords of each study, ve articles were selected [10][11][12][13][14] . The study selection process was visually presented in Fig.…”
Section: Characteristics and Quality Of Selected Studiesmentioning
confidence: 99%
“…However, they were still considered to be of moderate quality, scoring 5 or 6 points. HWE was detected in the asthmatic patients and controls in all studies [10][11][12][13][14] . All studies suggested that the distribution of genotypes in the controls was consistent with HWE except one study [10] , as shown in Table 3.…”
Section: Characteristics and Quality Of Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation